The gift of fear : survival signals that protect us from violence - De Becker, Gavin (Back Bay Books, Little, Brown and Company, 2021)
Covering all the dangerous situations people typically face -- street crime, domestic abuse, violence in the workplace -- de Becker provides real-life examples and offers specific advice on restraining orders, self-defense, and more. But the key to self-protection, he demonstrates, is learning how to trust -- and act on -- our own intuitions.